ZnO(N)-Spiro-MeOTAD hybrid photodiode: an efficient self-powered fast-response UV (visible) photosensor - Game, Onkar; Singh, Upendra; Kumari, Tanya; Banpurkar, Arun; Ogale, Satishchandra (Nanoscale, 2014)
Organic-inorganic hybrid photo-detectors with a self-sufficient mode of operation represent a research area of great current interest. In most efficient photodetectors and optoelectronic devices compound semiconductors containing toxic elements such as Cd, As, Te, S, Se etc. are used and these are also expensive. Hence there is also a rapidly growing interest in replacing these with environmentally friendly and earth-abundant materials. Herein, we report a facile solution-processed fabrication of a self-powered organic-inorganic hybrid photodetector using n-type oriented ZnO nanorods and p-type Spiro-MeOTAD semiconductor. ZnO is eco-friendly and earth-abundant, and Spiro-MeOTAD is nonhazardous. We show that the latter has far less toxicity than the toxic elements stated above. This visible blind UV photodetector shows high sensitivity (10(2)) and a UV/visible rejection ratio of 300. It also exhibits fast response times of tau(rise) similar to 200 mu s and tau(fall) similar to 950 mu s. Importantly, with a small modification of nitrogen incorporation in ZnO one can also realize a highly-sensitive self-powered visible light photodetector with at least 1000% (or higher) improvements in quality factors (photocurrent/sensitivity/response time) as compared to previously reported organic-inorganic hybrid photo-detectors based on metal-chalcogenides (CdS-PANI or CuInSe2-P3HT). Interestingly, the broadband sensitivity of such N:ZnO-Spiro-MeOTAD photodiode enables sensing of low intensity (similar to 28 mu W cm(-2)) ambient white light with a high photocurrent density of 120 nA cm(-2) making it an efficient ambient white light detector.

Aqueous dispersions of lipid nanoparticles wet hydrophobic and superhydrophobic surfaces - Kumar, Manoj; Kulkarni, Mayuresh A.; Chembu, Narendiran G.; Banpurkar, Arun; Kumaraswamy, Guruswamy (Soft Matter, 2018)
Efficient delivery of aqueous sprays to hydrophobic surfaces is the key technological challenge in a wide variety of applications, including pesticide delivery to plants. To account for losses due to bouncing of pesticide sprays off hydrophobic leaf surfaces, a large excess of pesticide is typically employed, resulting in environmentally hazardous run-offs that contaminate soil and ground water. We demonstrate that aqueous dispersions of glycerol monooleate nanoparticles, called cubosomes, wet hydrophobic and superhydrophobic surfaces and adhere to them. Cubosomes comprise glycerol monooleate lipid molecules self-assembled into a double diamond cubic phase, that form stable aqueous dispersions that are sterically stabilized using amphiphilic block copolymers. We use high speed imaging to monitor the spreading and retraction of aqueous drops impinged on model hydrophobic substrates and on superhydrophobic lotus leaves. We show that cubosomes diffuse to hydrophobic substrates and reorganize to form a thin, approximate to 2 nm adsorbed lipid layer during the millisecond time scales that characterize drop impact. This adsorbed film drastically reduces the water contact angle, transforming the hydrophobic surface to hydrophilic, thus facilitating retention of the aqueous drop on the surface. Aqueous drops of cubosomes impinged at low velocities on inclined natural superhydrophobic lotus leaf surfaces do not roll off, unlike drops of water or surfactant solutions. When sprayed on inclined lotus leaves, corresponding to the case of high velocity drop impingement, cubosome dispersions form a continuous wetting film. Our results have important implications for efficient, environment-friendly delivery of pesticide sprays.

Effects of gamma irradiation on non-polar GaN films deposited on sapphire using pulsed laser deposition - Rajgoli, Tahir; Sant, Tushar; Jejurikar, Suhas M.; Hinge, Sandip; Banpurkar, Arun; Dahiwale, S. S.; Late, Datta (Applied Surface Science, 2024)
The GaN films/layers exposed to gamma-radiations is known to harvest defects and vacancies in the crystals producing donor, acceptor and recombination centers within the bandgap. Therefore it is important to investigate and study the gamma- ray irradiation effects on various physical and chemical properties of a material before any optoelectronic and/or electronic devices are being fabricated. To avoid Stark effect which is observed in most of the optoelectronic devices fabricated using GaN films grew along polar face, use of non-polar GaN films is suggested by researchers. To address such issues the article reports the investigations of physical and chemical properties of non-polar GaN films grown on polar substrate using pulsed laser deposition, which were exposed to the 60Co gamma rays varying dose values. Resistive nature against the impairment of the films caused by gamma-rays observed herewith is highly encouraging, suggesting the use of non-polar GaN films as radiations harden material suitable for fabricating new generation gamma-ray detectors. To our knowledge very limited information is available that report such investigations.
Keywords: Gallium nitride; Gamma rays; PL emission; pulsed laser deposition

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane